Principles and examples for the allocation of scarce resources among economic sector - Moigne G. le; Dinar A. (Aspects économiques de la gestion de l'eau dans le bassin méditerranéen, 1997)
Water resources have been usually allocated to ensure sufficient quantity for human consumption and food production, addressing mainly equity issues. Considerations of efficiency have not always been incorporated. Water scarcity and quality have become a major problem in many countries that are beginning to appreciate water as an economic good. This paper addresses some of the principles of allocation scarce water resources among sectors. Several allocation mechanisms such as marginal cost pricing, allocation by a social planning (public allocation), and allocation by market forces are described. Examples of these mechanisms are provided and advantages and disadvantages are discussed. The paper also offers examples of how countries within the Mediterranean littoral put economic principles in the allocation of water into effect
Atelier sur les Aspects Economiques de la Gestion de l'Eau dans le Bassin Méditerranéen, 1995/05/17-19, Marrakech (Morocco)